A mezőgazdasági termelés hatására a felszíni vizekbe jutó pontszerű és diffúz szennyezés modellezési lehetőségei - Tankovics, András; Pokornyik, Norbert (Acta Scientiarum Socialium, 2013)
Available models for calculating point and diffuse source water pollution of agriculture With the development of technology for controlling point source pollution, the diffuse source pollution issues have become increasingly prominent worldwide. Because of the wide range, difficult control and complex uncertainties involved in simulation processes, diffuse source pollution control has become a hotspot in the area of water pollution control. Agriculture can contribute to water quality deterioration through the release of sediments, pesticides, animal manure and fertilizers. The aim of this study was to review the modeling technologies of the diffuse agricultural water pollution.
Keywords: diffuse water pollution; pollution models; agriculture; phoshporus; nitrogen